Revenue- versus spending-based consolidation plans: The role of follow-up - Roel Beetsma; Oana Furtuna; Massimo Giuliodori (European Central Bank (ECB), 2018)
The literature on fiscal multipliers finds that spending-based fiscal consolidations tend to have more benign macro-economic consequences than revenue-based consolidations. By directly comparing ex-post data with consolidation plans, we present evidence of a systematically weaker follow-up of spending-based consolidation plans. Next, using a newly-developed dataset of consolidation announcements, panel VAR regressions confirm the weaker follow-up of spending-based plans and their more benign macro-economic effects compared to those of revenue-based plans. We disentangle the role of the difference in follow-up from that of the difference in the composition of revenue- and spending-based consolidations. While the latter channel, which works through the difference between revenue and spending multipliers, explains the largest fraction of the difference in economic trajectories, the difference in follow-up plays a non-negligible role as well.
Keywords: E21; E62; H5; 330; fiscal consolidation announcements; follow-up; fiscal multipliers; panel vector auto-regression; narrative identification